2013
DOI: 10.5120/10573-5612
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuations in Stock Market Prices: What went wrong, its Implications to Nigerian Economy?

Abstract: The Nigerian stock market recently witnessed a continuous drop in the All-Share Index and volume of traded securities. The stock market indices have moved far relative to their previous year's levels and banks and markets suddenly become clearly unstable or strained to the point where it may collapse. In order to forestall future happenings, this work therefore defines a method of training that provides a forecast of stock growth over a period of 52 weeks. The earnings per share, price earnings ratio and the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…However, the recent experienced showed that the higher the expected profit, the higher the risk implication. (Kou, Chen, & Hwang, 2001;Vincent & Bamiro, 2013) Thus, numerous investigations gave rise to different decision support systems for the sake of providing the investors with an optimal prediction. With the huge availability of stock information, made possible by the internet, the task of the investor has been made more difficult, as he will have to collect, analyse, filter and make correct decision from several information.…”
Section: Problem Statementmentioning
confidence: 99%
“…However, the recent experienced showed that the higher the expected profit, the higher the risk implication. (Kou, Chen, & Hwang, 2001;Vincent & Bamiro, 2013) Thus, numerous investigations gave rise to different decision support systems for the sake of providing the investors with an optimal prediction. With the huge availability of stock information, made possible by the internet, the task of the investor has been made more difficult, as he will have to collect, analyse, filter and make correct decision from several information.…”
Section: Problem Statementmentioning
confidence: 99%